Правові важелі протидії інформаційним загрозам : міжнародний і вітчизняний досвід - Кормич, Борис Анатолійович; Кормич, Борис Анатольевич; Kormich, B. (My University, 2011)
The article provides the analyses of the forms and types of the threats in the informational sphere. The main aspects of the international and national level of legal regulation of the informational security are also reviewed.
Кормич Б. А. Правові важелі протидії інформаційним загрозам : міжнародний і вітчизняний досвід / Б. А. Кормич // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. – Одеса : Фенікс, 2011. – Вип. 42. – С. 80 - 89.
Keywords: інформаційні загрози; інформація; інформаційна безпека; Генеральної Асамблеї ООН; Генеральная Асамблея ООН; информационная безопасность; информация; информационные угрозы; UN General Asambleya; information Security; information; information threats